Leaving or Staying “Home” in a Time of Rupture: International Students’ Experiences of Loneliness and Social Isolation during COVID-19 - Wallen, Linnea; Sagan, Olivia; Scally-Robertson, Mhairi (Journal of International Students, 2024)
During COVID-19, international students were faced with the decision of remaining in their country of study or returning to their home countries, with little knowledge of when they would next be able to return or leave. Both choices left the students vulnerable to feelings of loneliness and social isolation. This paper examines how international students at a Scottish university experienced and navigated leaving or staying “home” and how loneliness and social isolation characterised these experiences. We further contextualise these experiences through Holbraad et al.’s (2019) prism of “rupture”. The data were generated between February-July 2021 through semi-structured focus groups and qualitative questionnaire comments and were analysed through Thematic Analysis. We discuss three themes: 1) Liminal Friends and Strangers, 2) Sense of Home and Family, and 3) Staying or Leaving the Country. The study contributes to the expanding body of research on experiences of loneliness and social isolation amongst international students.